Ensuring Universal Access to Modern Energy Services in Times of Pandemic Related Disruptions: Legal Challenges and Potential Responses - Olawuyi, Damilola; Nalule , Victoria R. (Journal of Sustainable Development Law and Policy, 2025)
The significant disruptions to global energy markets across the world, in light of the COVID-19 pandemic, has shown that without robust law and governance frameworks to mitigate and manage pandemic-related disruptions to energy supply, global efforts to achieve the United Nations Sustainable Development Goals may be stifled. This article examines legal and governance aspects of designing and implementing disaster risk reduction and resilience (DRRR) frameworks to ensure the security of energy supply in times of pandemic related disruptions. Various legal and institutional challenges that arise with extant DRRR frameworks, such as weak conceptualization of pandemic related risks in extant legislation; preexisting patterns of uneven energy access; gaps in data collection and sharing with respect to pandemic risks; inadequate crosssectoral coordination amongst institutional actors, and resource limitations are examined in order to identify the ways in which an integrative legal framework on disaster management and resilience planning can help close these gaps. The study suggests that clear and comprehensive legislation that recalibrate the scope of energy disruptions and improves data collection and cross-sectoral knowledge sharing by relevant institutional actors are significant steps towards protecting the integrity and resilience of modern energy systems in times of disruptive events such as pandemics.